2012
DOI: 10.1002/bdd.1815
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interactions among major bioactive components in Radix Scutellariae via metabolic competition

Abstract: Baicalein (B), wogonin (W) and oroxylin A (OA) are major components in Radix Scutellariae with similar pharmacokinetic properties. Due to the co-presence of these three flavones in herbal formulations for Radix Scutellariae, they are likely consumed together. The aim of this study is to investigate whether the pharmacokinetics of individual flavones is influenced by each other and the underlying mechanism of the interaction. Various systems were utilized in the current study including a rat in vivo study, a Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…For example, it was found that the absorption of baicalein, wogonin and oroxylin A were higher in Scutellaria baicalensis extract than when administrated individually. [69] Similar results were observed for cryptotanshinone and tanshinone IIA coexisting in Salvia miltiorrhiza Bge. [70] The same compound in different herbs may have different bioavailability due to the complexity of the constituents of herbal medicines, such as paeonol, whose bioavailability in Paenia suffruticosa Andr.…”
Section: Herbal Interaction Study At the Level Of Intestinal Absorptionsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, it was found that the absorption of baicalein, wogonin and oroxylin A were higher in Scutellaria baicalensis extract than when administrated individually. [69] Similar results were observed for cryptotanshinone and tanshinone IIA coexisting in Salvia miltiorrhiza Bge. [70] The same compound in different herbs may have different bioavailability due to the complexity of the constituents of herbal medicines, such as paeonol, whose bioavailability in Paenia suffruticosa Andr.…”
Section: Herbal Interaction Study At the Level Of Intestinal Absorptionsupporting
confidence: 72%
“…According to the latest reports, studies on the interactions among components in a single herb or different herbal medicines have been summarized in Table 2 [66][67][68][69][70][71][72][73][74][75][76][77][78] , within TCM preparations that have been summarized in Table 3 [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] .…”
Section: Herbal Interaction Study At the Level Of Intestinal Absorptionmentioning
confidence: 99%
“…And so, we think it’s reasonable to speculate that S. baicalensis and its active component BB (BB) have ameliorative effect on CPT-11-induced gastrointestinal toxicity. Because baicalin is absorbed as the form of baicalein and they have “enterohepatic circulation” phenomenon in vivo (Li et al, 2012), rats in group T/BB were administrated the mixture of BB. Mean metabolic position had been used in PCA trajectory plots to map the metabolic changes in chemicals exposure by Nicholson et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutically, they are both indicated for inflammatory diseases, with inhibition on cyclooxygenase-2 (COX-2) being one of their major antiinflammatory mechanisms (Lin and Shieh, 1996;Vane, 1971). Pharmacokinetically, they share similar metabolic pathways: the bioactive components of SR and the majority of the NSAIDs are reported to undergo extensive hepatic Phase II metabolisms (Kiang et al, 2005;Li et al, 2012). These similarities may increase the opportunity of co-administration by patients and, at the same time, the potential of pharmacokinetic and/or pharmacodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%